ANALISIS NILAI TELIGIUS DALAM NOVEL TENGGELAMNYA “KAPAL VAN DER WIJCK” KARYA HAMKA - Della Putri Rahmadani (FKIP, Universitas Palangka Raya, 2023)
This study aims to describe, analyze, identify, and conclude about the religious values contained in Hamka's novel Tenggelamnya Kapal Van Der Wijck. This study uses a qualitative descriptive research method. The subject of this research is the Novel Sinking of the Van Der Wijck Ship written by Hamka. The power collection techniques used are reading techniques, creating data screening instruments and coding. The data obtained from this study were analyzed using content analysis. The results of the study show that in the novel Tenggelamnya Kapal Van Der Wijck there are three things related to religious values, namely the relationship between humans and God, humans and humans and humans and nature.